Presentation of Chinese Rural Society in Documentary Films on Rural Revitalization : An Analysis - Qu, Lei; Teo, Miaw Lee; Candida, Jau Emang (Journal of Research in Social Science and Humanities, 2023)
On January 1, 2011, in order to promote a better global understanding of China, China Central Television's Documentary Channel began broadcasting 24 hours a day worldwide. With the launch of the documentary channel, documentaries officially entered the field of vision of ordinary Chinese citizens, serving as a medium to record the lives of the Chines e populace and presenting their authentic everyday lives and personal stories to the world. This also left behind precious social memories in rapidly developing China (Wu Haili, 2013). As an agricultural powerhouse, rural areas constitute a significant component of Chinese society, retaining rich historical and cultural traditions. Farmers carry immense spiritual strength and touching narratives, prompting numerous socially responsible documentary filmmakers to turn their cameras towards China's countryside and its people. This effort has led to the creation of a substantial number of outstanding documentary films centered on Chinese rural themes. Chinese rural themed documentary films have emerged as prime artistic samples reflecting rural societal conditions and transformations. This paper focuses on the rural society portrayed in documentary films with rural themes and analyzes how these films depict various aspects of China s rural society, such as economic production, living environment, education, and employment, within the context of rural revitalization documentaries. Through the analysis and examination of this theme, the paper elucidates the genuine face of China's rural society and the monumental changes depicted in these documentary films, providing a comprehensive perspective and a macroscopic view for the creation of related documentary works (Mao Yurong, 2022).